Wybór modelu oraz zmiennych do modelu w ujęciu bayesowskim - Biskup, Dariusz (Bayesian Approach to Model and Varriable Selection, 2006)
The paper describes Bayesian approach to statistical model identification and to the problem of variable choice in linear regression model. The model choice bases on the criterion of posterior probability of model reliability which is understood as the accurateness of identification of data generation mechanism. Theoretical basis for this approach have been presented as well as several examples of its application.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1140, s. 87-97